2012
DOI: 10.1186/1471-2296-13-94
|View full text |Cite
|
Sign up to set email alerts
|

What determines the income gap between French male and female GPs - the role of medical practices

Abstract: BackgroundIn many OECD countries, the gender differences in physicians’ pay favour male doctors. Due to the feminisation of the doctor profession, it is essential to measure this income gap in the French context of Fee-for-service payment (FFS) and then to precisely identify its determinants. The objective of this study is to measure and analyse the 2008 income gap between males and females general practitioners (GPs). This paper focuses on the role of gender medical practices differentials among GPs working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…Homaie Rad et al without mentioning the reasons for income inequality among different gender groups, pointed out that there was a significant difference between the income of women and men employed in the health sector of Iran [5]. Several studies, which are consistent with the results of the present study, have identified the main cause of income inequality among male and female GPs in their working hours [16, 17, 25, 26]. Nevertheless, the results of Duckett’s study in the United States, which contradict the interpretation of the results of the present study, showed that, apart from other factors such as working hours, there is a significant difference between the income of female and male employees in the health sector.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Homaie Rad et al without mentioning the reasons for income inequality among different gender groups, pointed out that there was a significant difference between the income of women and men employed in the health sector of Iran [5]. Several studies, which are consistent with the results of the present study, have identified the main cause of income inequality among male and female GPs in their working hours [16, 17, 25, 26]. Nevertheless, the results of Duckett’s study in the United States, which contradict the interpretation of the results of the present study, showed that, apart from other factors such as working hours, there is a significant difference between the income of female and male employees in the health sector.…”
Section: Discussionsupporting
confidence: 88%
“…A study in Australia showed that GPs who worked in outer regions or rural areas and those who worked in personal office had higher income [16]. Another study in France demonstrated that male GPs had higher income than females, this result was explained with respect to different workloads [17].…”
Section: Introductionmentioning
confidence: 99%
“…The primary care physician (PCP) workforce in many industrialized nations is increasingly female. In several industrialized countries, the proportion of PCPs who are women has doubled or nearly doubled over the last 30 years [ 1 , 2 ]. Globally, 32% of all physician graduates worldwide are female, and that percentage is higher, on average, in family medicine [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 This discrepancy in workload between the sexes identified in this study on chiropractic medicine in Switzerland has been described in other medical professions in the same way and is consistent with the study mentioned earlier about the situation in other countries relating to the ongoing feminization in medicine. 16,17 It is most likely caused by the higher number of female doctors working part time compared with their male counterparts. 9,10 As mentioned earlier, for female doctors, working part time seems to have a negative influence on their career.…”
Section: Discussionmentioning
confidence: 99%
“…11 These same trends are also occurring in other countries, with women physicians more likely to work part time and participate in group practices. [8][9][10][16][17][18][19] Because there is an obvious majority of female students currently studying chiropractic medicine at the University of Zürich, similar to their medical counterparts, it is important to know what effect, if any, this will have for patients and their chiropractic care in the future. Therefore, the purpose of this study is to identify differences in the practice characteristics and treatment techniques of female and male chiropractors and to discuss what impact these differences might have for the profession in the coming years.…”
Section: Introductionmentioning
confidence: 99%